Comparative Nutritional Characterization of a Novel Formulated Composite Milk Alternative and a Conventional Infant Formula : (Corrected Proof) - Ani, Onuabuchi Nnenna; Ujah, Innocent Izuchukwu; Akpata, Ebere Immaculata; Oguazu, Chinenye Enoch (The North African Journal of Food and Nutrition Research, 2026)
Background: The beverage industry has experienced a substantial surge in the development of composite milk alternatives (CMAs), precipitated by shifting dietary preferences and specific nutritional requirements. However, the increasing utilization of these alternatives in infant nutrition has prompted critical inquiries regarding their nutritional adequacy and bioequivalence to standardized formulas.Aims: This study aimed to perform a comparative evaluation of the proximate, phytochemical, vitamin, and mineral profiles of a novel formulated CMA (plant-animal-based, formulated using soybean, tiger nut, peanut, cashew nut, dry fish, crayfish, and dates) against a conventional commercial infant formula (NAN).Materials and methods: Raw materials were processed, and homogenized in standardized proportions. Analytical characterization was conducted using established biochemical methods for proximate analysis and micro-/macro-nutrient quantification. Statistical significance was determined using a two-tailed unpaired Student's t-test, assuming equal variance, with the threshold for significance set at α = 0.05.Results: Distinct compositional divergence was observed between the formulated CMA and the commercial control. The CMA exhibited significantly higher concentrations (p